Elabela Protects Spontaneously Hypertensive Rats From Hypertension and Cardiorenal Dysfunctions Exacerbated by Dietary High-Salt Intake - Xavier Sainsily; Xavier Sainsily; Xavier Sainsily; David Coquerel; David Coquerel; Hugo Giguère; Hugo Giguère; Lauralyne Dumont; Lauralyne Dumont; Kien Tran; Kien Tran; Christophe Noll; et al. (Frontiers Media S.A., 2021)
Objectives: Arterial hypertension, when exacerbated by excessive dietary salt intake, worsens the morbidity and mortality rates associated with cardiovascular and renal diseases. Stimulation of the apelinergic system appears to protect against several circulatory system diseases, but it remains unknown if such beneficial effects are conserved in severe hypertension. Therefore, we aimed at determining whether continuous infusion of apelinergic ligands (i.e., Apelin-13 and Elabela) exerted cardiorenal protective effects in spontaneously hypertensive (SHR) rats receiving high-salt diet.Methods: A combination of echocardiography, binding assay, histology, and biochemical approaches were used to investigate the cardiovascular and renal effects of Apelin-13 or Elabela infusion over 6 weeks in SHR fed with normal-salt or high-salt chow.Results: High-salt intake upregulated the cardiac and renal expression of APJ receptor in SHR. Importantly, Elabela was more effective than Apelin-13 in reducing high blood pressure, cardiovascular and renal dysfunctions, fibrosis and hypertrophy in high-salt fed SHR. Unlike Apelin-13, the beneficial effects of Elabela were associated with a counter-regulatory role of the ACE/ACE2/neprilysin axis of the renin-angiotensin-aldosterone system (RAAS) in heart and kidneys of salt-loaded SHR. Interestingly, Elabela also displayed higher affinity for APJ in the presence of high salt concentration and better resistance to RAAS enzymes known to cleave Apelin-13.Conclusion: These findings highlight the protective action of the apelinergic system against salt-induced severe hypertension and cardiorenal failure. As compared with Apelin-13, Elabela displays superior pharmacodynamic and pharmacokinetic properties that warrant further investigation of its therapeutic use in cardiovascular and kidney diseases.